Sensing the self : women's recovery from bulimia - Reindl, Sheila M., 1958- (Cambridge, Mass. : Harvard University Press, 2002)
While many books describe the descent into eating disorders and the resulting emotional and physical damage, this book describes recovery. Psychologist Sheila Reindl has listened to women's accounts of recovering. Reindl argues that people with bulimia nervosa avoid turning their attention inward to consult their needs, desires, feelings, and aggressive strivings because to do so is to encounter an annihilating sense of shame. Disconnected from internal, sensed experience, bulimic women rely upon external gauges to guide their choices. To recover, bulimic women need to develop a sense of self--to attune to their physical, psychic, and social self-experience. They also need to learn that one's neediness, desire, pain, and aggression are not sources of shame to be kept hidden but essential aspects of humanity necessary for zestful life. The young women with whom Reindl speaks describe, with great feeling, their efforts to know and trust their own experience.
Includes bibliographical references (p. [317]-326) and index.
Keywords: Bulimia; Women -- Health and hygiene; Eating disorders